From user perception to architecture.: Improving arrival and waiting spaces in primary healthcare centres (Journal of Accessibility and Design for All, 2025)
This research paper examines primary healthcare facilities in Montenegro, focusing on outpatient spaces - arrival infrastructure, outside spaces, and inside spaces. In Montenegro, primary health centres provide 80-85% of all health care services and are designed to serve patients within the defined local community. In these facilities, the maintainer of primary care is a chosen doctor (GP), a person most familiar with the patient's conditions and social background. Despite the personal service healthcare centres provide, the architectural expressions of the built facilities do not reflect the intimate nature or personalisation of this service. By examining the user experience and doing field research, we identified several shortcomings in these facilities' exterior and interior quality. Data was gathered through a questionnaire involving users and field research, encompassing large, medium, and small-sized healthcare centres. Participants initially expressed neutral perceptions of existing elements, but when given the opportunity to choose, they became more inclined to suggest improvements. The field study identified rather negative architectural aspects, including inconsistencies in performance across the facilities. The design primarily serves the functional requirements determined by the current capacity, whereas considerations regarding aesthetics and the users' comfort are often neglected. The findings highlight the need to align architectural design with user preferences, emphasising the significance of user-centric healthcare facility design in Montenegro and similar environments.